2013
DOI: 10.1146/annurev-physiol-030212-183802
|View full text |Cite
|
Sign up to set email alerts
|

The Adventitia: Essential Regulator of Vascular Wall Structure and Function

Abstract: The vascular adventitia acts as a biological processing center for the retrieval, integration, storage, and release of key regulators of vessel wall function. It is the most complex compartment of the vessel wall and is comprised of a variety of cells including fibroblasts, immunomodulatory cells (dendritic and macrophages), progenitor cells, vasa vasorum endothelial cells and pericytes, and adrenergic nerves. In response to vascular stress or injury, resident adventitial cells are often the first to be activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
354
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(374 citation statements)
references
References 161 publications
(222 reference statements)
9
354
1
10
Order By: Relevance
“…MOMA-2 staining revealing monocyte/ macrophage infiltration in aortic wall was determined in wild-type, endothelium-specific endothelin-1 overexpression (eET-1), colony stimulating actor-deficient (Csf1 cells), nerves, progenitor cells, and immune cells, including macrophages. 22 Perivascular fat is closely associated to the adventitia. Overexpression of ET-1 in endothelial cells caused an increase in monocyte/macrophage infiltration in the adventitia and associated perivascular fat, which is similar to findings in mice infused with Ang II or aldosterone.…”
Section: Csf1mentioning
confidence: 99%
See 1 more Smart Citation
“…MOMA-2 staining revealing monocyte/ macrophage infiltration in aortic wall was determined in wild-type, endothelium-specific endothelin-1 overexpression (eET-1), colony stimulating actor-deficient (Csf1 cells), nerves, progenitor cells, and immune cells, including macrophages. 22 Perivascular fat is closely associated to the adventitia. Overexpression of ET-1 in endothelial cells caused an increase in monocyte/macrophage infiltration in the adventitia and associated perivascular fat, which is similar to findings in mice infused with Ang II or aldosterone.…”
Section: Csf1mentioning
confidence: 99%
“…Vascular inflammation could be initiated and perpetuated in the adventitia, according to the outside-in hypothesis. 22 Increased expression of ET-1 in endothelium or within the adventitia could act in paracrine fashion directly on monocytes or macrophages or via other cells, such as the smooth muscle cells. In this study and previously, we found that a deficiency in CSF1 impaired monocyte/macrophage infiltration induced by ET-1, Ang II, and DOCA/salt in rodents, the latter a hypertensive model with an important ET-1-dependent component.…”
Section: Csf1mentioning
confidence: 99%
“…4,5 During the remodeling, pulmonary adventitial fibroblasts (PAFs) are highly activated and undergo phenotype switch characterized by excessive proliferation, migratory, and inflammatory activity. 6,7 Therefore, inhibition of the aberrant activation of PAFs may reverse the remodeling process of pulmonary vascular adventitia and have therapeutic potential for HPH.…”
mentioning
confidence: 99%
“…All the three layers of the arteries infected by the virus would show inflammatory cell infiltrate. The thickened adventitia is associated with inflammation of the vasa vasorum in the early VZV-vasculopathy [15,16]. These altered pathology lead to arterial caliber irregularities, and contractility Arterial or venous thrombosis of the lower libs due to VZVhypercoagulability.…”
Section: Resultsmentioning
confidence: 99%